Case Report: Dose-dependent response to oclacitinib in a dog with Sézary syndrome - Lym, Jungmin; Chae, Yeon; Kim, Sanggu; Lee, Sungjae; Koo, Yoonhoi; Kim, Hakhyun; Kang, Byeong-Teck; Kim, Soochong; Yun, Taesik (Frontiers in Veterinary Science, 2025)
Cutaneous epitheliotropic T-cell lymphoma (CETL) is a rare malignant canine skin tumor. Sézary syndrome, a rare and aggressive subtype of CETL, lacks established treatment guidelines in veterinary medicine. A 10-year-old, spayed female Yorkshire Terrier presented with multiple skin nodules, plaques, crusts, and pruritus. Histopathological and immunohistochemical evaluations confirmed CETL, and Sézary cells were identified in a peripheral blood smear, confirming Sézary syndrome. The dog was initially treated with oclacitinib 0.7 mg/kg twice daily. Marked clinical improvement was observed on day 15 with the disappearance of Sézary cells. However, by day 32, the skin lesions had worsened, and the oclacitinib dose was increased to 3 mg/kg twice daily. Subsequent improvements were noted within 12 days, although a relapse occurred on day 63. Immunohistochemical staining revealed moderate and diffuse cytoplasmic and nuclear expression of Janus kinase 1 (JAK1), an oclacitinib target. This case demonstrated that both low- and high-dose oclacitinib may offer temporary clinical benefits in dogs with Sézary syndrome, potentially via JAK1 inhibition. Although the duration of the response was limited, the survival period exceeded that of previously reported canine cases of Sézary syndrome. These findings support further investigation of Janus kinase inhibitors as therapeutic options for Sézary syndrome and other forms of CETL in veterinary patients.